EISCAT verification in the development of ionospheric tomography - I. K. Walker; J. A. T. Heaton; L. Kersley; C. N. Mitchell; S. E. Pryse; M. J. Williams (Annales Geophysicae, 1996)
This paper highlights the important role played by the EISCAT radar for verification in the development of tomographic techniques to produce images of ionospheric electron density. A brief review is given of some of the stages in the application of tomographic reconstruction techniques to the ionosphere. Results are presented to illustrate the effectiveness of the method in imaging ionospheric structures at high latitudes. In addition, the results include the first tomographic image of the ionosphere for a region extending from mid-latitudes over mainland Scandinavia to high latitudes above Svalbard.